A diagnostic algorithm for persistence of very early inflammatory arthritis: the utility of power Doppler ultrasound when added to conventional assessment tools. Issue 2 (8th April 2009) - Freeston, J E; Wakefield, R J; Conaghan, P G; Hensor, E M A; Stewart, S P; Emery, P
Abstract : Objectives: The aim of this study was to assess the value of power Doppler ultrasound (PDUS) in combination with routine management in a cohort of patients with very early inflammatory arthritis (IA). Methods: 50 patients with ⩽12 weeks of inflammatory symptoms with or without signs had clinical, laboratory and imaging assessments. Diagnosis was recorded at 12 months. Assuming a 15% pre-test probability of IA, post-test probabilities for various assessments were calculated and used to develop a diagnostic algorithm. Results: All patients positive for rheumatoid factor (RF) and/or cyclic citrullinated peptide (CCP) developed persistent IA, so the added value of PDUS was assessed in the seronegative (RF and CCP negative) group. The probability of IA in a seronegative patient was 6%. The addition of clinical and radiographic features raised the probability of IA to 30% and, with certain ultrasound features, this rose to 94%. Conclusions: In seronegative patients with early IA, combining PDUS with routine assessment can have a major impact on the certainty of diagnosis.